Ferrocene‐Initiated Oxidative Cyclization of Benzaldehyde with Alkyne: New Strategy to Substituted Indenones. Issue 16 (10th April 2019) - Feng, Yadong; Zhang, Hong; Yu, Yunliang; Yang, Lei; Cui, Xiuling
Abstract : A ferrocene‐initiated oxidative cyclization of benzaldehyde with alkyne was successfully developed as a novel strategy for direct access to substituted indenones in high yields. The commercially available and cheap ferrocene was employed as an initiator. This transformation could proceed smoothly with a low initiator loading (0.5 mol‐%) and provide the titled products up to 90 % yield with atom‐, step‐economy and good substrates tolerance. The indenones obtained would be important building blocks in organic synthesis. Abstract : A ferrocene‐initiated oxidative cyclization of benzaldehyde with alkyne was successfully developed as a novel strategy for the direct access to substituted indenones in high yields. The commercially available and cheap ferrocene was employed as an initiator.